Development of macroreological model of strain relaxation in lubricating film on friction surface in the presence of fullerenes - Кравцов, А. Г. (Problems of Tribology, 2019)
In the article the development of the macroreоlogical model of relaxation of stresses on the spots of the actual contact of tribosystems in the presence of fullerenes in the lubricant is presented. Macroreological model is represented as second order differential equations and their solutions. A working hypothesis is formed to reduce the frictional forces in tribosestems in the presence of a dispersed phase in a lubricant, which will be further confirmed by theoretical models and experimentally. The general structural feature of liquid lubricants in the presence of fullerenes in them as functional additives is that clusters and micelles are formed in the volume of the liquid. The formation of clusters and micelles in the lubricant depends directly on the concentration of fullerenes that are introduced into the lubricant, and the oleic acid molecules. The forces of electrostatic interaction between disperse phase units and friction surfaces were considered. In this case, the concentration of aggregates in the field of action of the electrostatic forces of the surface of the friction will be greater than at a distance from the surface, where the field does not work. In the future, the microresimal model of relaxation of stresses on the points of actual contact with the presence of fullerenes in the lubricant will be developed, and a simulation of the stress relaxation dynamics and the coefficient of friction in the presence of fullerenes in the lubricant will be developed.